Karakter muslim / Umar Sulaiman Al-Asyqar ; penerjemah, Moh. Nurhakim ; penyunting, Fauzan Al Anshori - AL-ASYQAR, Umar Sulaiman; Nurhakim, Moh; Al Anshori, Fauzan (gema Insani Press, 1995)
69 hlm. 18 cm.